Identification of promising sunflower (Helianthus annuus L.) inbred lines for oil and quality parameters: Identification of promising sunflower (Helianthus annuus L.) inbred lines for oil and quality parameters - PRADUMAN YADAV,; H P MEENA,; K S V P CHANDRIKA,; A VISHNUVARDHAN REDDY, (Journal of Oilseeds Research, 2020)
Improvement of oil content and oil quality are the major goals in sunflower research. In the present study, a set of 60 sunflower inbred lines were evaluated for oil content and fatty acid profile. Oil content in the inbreds, ranged from 28.13 (GPR-58) to 41.03% (RHA-6D-1 and AKSFI-42-1). Nine inbred lines showed more than 38 percent oil content and one line showed high linoleic acid content of 70.2% (RHA-272). Two other inbred lines viz., AKSFI-52- 2 (10.47%) and CSFI-5033 (10.27%) recorded high stearic acid content.